Appropriateness of radiographic imaging ordered by emergency physicians: a knowledge-based survey - Chhotani, Abdul Ahad; Iqbal, Sannia Perwaiz; Emaduddin Siddiqui (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the knowledge of physicians working in the emergency department in choosing appropriate diagnostic imaging in different clinical scenarios. Method: The cross-sectional study was conducted at the Emergency Department of the Aga Khan University Hospital, Karachi, from January 3 to July 2, 2018, and comprised registered medical officers, residents, and consultants of either gender involved in emergency care decision-making. Data was collected using a structured questionnaire that had 10 clinical scenarios based on the American College of Radiology Appropriateness Criteria guidelines. Data was analysed using SPSS 17. Results: Of the 82 participants, 50(61%) were males and 32(39%) were females. The overall mean age was 34.06±6.42 years. Of the total, 50(61%) subjects had appropriate knowledge regarding imaging. The overall mean number of correct responses was 6.90±1.20. Those belonging to the Emergency Medicine specialty had significantly higher odds of having appropriate knowledge compared to participants belonging to other specialties when adjusted for age, gender, position of practice and years of Emergency Medicine training (Odds ratio: 4.73; 95% confidence interval: 1.07-20.91). Conclusion: Physicians belonging to the Emergency Medicine specialty were more likely to have adequate knowledge regarding imaging appropriateness compared to other specialties. Key Words: Appropriateness criteria, Emergency medicine, American College of Radiology, Resident education, Guidelines.